2021
DOI: 10.1002/glia.24055
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale electron microscopic volume imaging of interfascicular oligodendrocytes in the mouse corpus callosum

Abstract: Single oligodendrocytes produce myelin sheaths around multiple axons in the central nervous system. Interfascicular oligodendrocytes (IOs) facilitate nerve conduction, but their detailed morphologies remain largely unknown. In the present study, we three‐dimensionally reconstructed IOs in the corpus callosum of adult mouse using serial block face scanning electron microscopy. The cell bodies of IOs were morphologically polarized and extended thick processes from the cytoplasm‐rich part of the cell. Processes o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…The advantage of joint LSM and super-resolution TDI is that we are better able to interpret the fine-structure resolved in Figs 4B and E compared to previous state-of-the-art work (e.g., figure 5C from [36]) In corpus callosum and other tracts. The fine strands are consistent with fascicles of myelinated axons that contrast with darker interfascicular callosal oligodendrocytes [37] [38] ( Fig 4B and E ). Some of the strands are nearly 1 mm long and have an apparent diameter of 15–30 μm.…”
Section: Resultssupporting
confidence: 53%
“…The advantage of joint LSM and super-resolution TDI is that we are better able to interpret the fine-structure resolved in Figs 4B and E compared to previous state-of-the-art work (e.g., figure 5C from [36]) In corpus callosum and other tracts. The fine strands are consistent with fascicles of myelinated axons that contrast with darker interfascicular callosal oligodendrocytes [37] [38] ( Fig 4B and E ). Some of the strands are nearly 1 mm long and have an apparent diameter of 15–30 μm.…”
Section: Resultssupporting
confidence: 53%
“…It is unknown how glial cells are distributed in regions of axon crossing—i.e., whether they are arranged in arrays of intersecting glial rows or randomly distributed. This question has notable biological implications ( 28 ): If the glial framework persists in regions of fiber crossing, this strengthens the assumption that the spatial organization of glial cells has functional implications, providing evidence that glial cells are tract-specific and are not shared across tracts. We found evidence supporting the persistence of the glial framework in regions of fiber crossing: First, our ability to obtain maps similar to those derived from PLI with only Nissl-stained images suggested that the glial framework is a brainwide feature.…”
mentioning
confidence: 63%
“…The glial framework-the patterned spatial organization of glial cells in the white matter-has been described in only a handful of pathways, namely the rat fimbria (13), the mouse corpus callosum (28) and the vervet corpus callosum (29). Additionally, Pandya and Schmahmann (3) briefly mentioned the glial framework (which they call the "glial matrix") in the context of the ILF and the nearby tracts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While many of these early oligodendrocyte lineage cells degenerate and are lost during development ( Hughes and Stockton, 2021 ), surviving cells differentiate into myelinating and matured oligodendrocytes expressing markers such as myelin basic protein (MBP) and myelin-associated oligodendrocytic basic protein (MOBP), and produce myelin sheathes around multiple axons localized at the vicinity of their extended processes. The extension of process could be primarily limited but not restricted to a small range; oligodendrocytes do not myelinate axons closest to cell body, as observed with intrafascicular oligodendrocytes in the white matter ( Tanaka et al, 2021 ).…”
Section: Oligodendrocyte Morphology and Its Contribution To Neural In...mentioning
confidence: 86%